Käsityötä, kotiteollisuutta ja sosiaalihuoltoa : työtupa Aunuksessa 1941–1944 - Laitinen, Anna (Helsingfors universitet, 2010)
When Finland occupied East Karelian territories in Soviet Union during The Continuation War (1941 1944) Finnish people had also to take care of the inhabitants of the occupied East Karelia. For example there was a lack of clothes and shoes during the wartime. In order to facilitate clothing situation and to provide more opportunities to work for women, Finnish people founded some workshops in East Karelia. Workshops also helped to collect East Karelian craft products. One of the workshops was founded in the city of Olonets in October 1941 and it was in operation until June 1944. This workshop is the subject of this thesis. The aim of this thesis is to find out with the microhistorical approach what kind of functions the workshop of Olonets had during The Continuation War and who worked in the workshop. In this thesis I also examine women's crafts in the Olonets workshop and their meaning during the wartime. I collected the material of this thesis from different places. In February 2010 I interviewed Talvikki Lausala, the leader of the Olonets workshop, who worked in the Olonets from May 1942 to June 1944. From the Virkki Käsityömuseo I looked for objects which have been made in the workshop of Olonets. Tyyne-Kerttu Virkki collected crafts from the East Karelia when she was working in the area and in the workshop from 1941 to 1944. Archive material I found from the Finnish National archive and from the archive of the Tyyne-Kerttu Virkki -Foundation. East Karelian women and girls who were not able to do anything else came to work in the Olonets workshop. If women could not go to work outside of home, they had an option to do the same crafts at home. There were three Finnish women, Tyyne-Kerttu Virkki, Talvikki Lausala and Sofi Nyrkkö, who worked and led in the workshop of Olonets. In addition to the workshop, there was a dress maker's atelier in which clothes were made to order and soldiers uniforms were repaired, a small museum and a shop to sell products of the workshop. Craft products were also exported to ...